How electronic emergency and disaster system can reduce nursing workload? - Mesa, Nofita Dewi Kok; Wihastuti, Titin Andri; Nugroho, Fajar Ari; Supriyadi, Muchamad (Intelektual Pustaka Media Utama, 2023)
Prehospital care is an emergency medical service (EMS) administered outside of the hospital. Time-consuming documentation of medical records is one of the tasks that prehospital nurses have to complete. It requires the development of innovations to improve prehospital care. To enhance prehospital treatment, innovations must be created. The purpose of this study is to ascertain whether the emergency and disaster electronic handling system application (SPEED) decreases the time nurses spend recording patient records. A total of 54 samples will be randomly separated into two groups as part of the study's true experimental design with crossed over method. Each of the three study sessions lasts for three weeks to finish. Group B received the first period of the paper-based intervention, whereas group A received the SPEED intervention. Group B will get the SPEED intervention following the washout period (second period), whereas group A will receive a paper-based intervention (third period). The independent t-test showed that the SPEED application was more efficient than paper-based using a mean difference value of 25.22 and a sig (2-tailed) value of 0.00. The SPEED application can make nurses' jobs easier and lighten their prehospital nurses' mental, physical, and time demands.